Implementation of AHP and Fuzzy Topsis Methods with Techno Economic Analysis Selection of Appropriate Technology for Waste Management Case Study University of Indonesia - Panji Utomo; Adi Surjosatyo (Journal Research of Social Science, Economics, and Management, 2024)
The "Zero Waste City" program is a waste management policy initiative in Depok City that has been implemented from 2016 to 2024. The primary objective of this program is to make the entire Depok City area free from all types of waste. However, the program's implementation faces challenges, leading to some areas in Depok City still struggling with waste issues. Universitas Indonesia, as a higher education institution located in Depok City, acknowledges the waste-related challenges in its surrounding environment. Therefore, the university is committed to actively participating in solving waste issues originating from its campus environment. This research aims to address waste issues at the source, particularly by applying appropriate technology based on the criteria and sub-criteria at Universitas Indonesia. This step is expected to contribute to reducing waste-related problems in Depok City and serve as an example of effective waste management from its source. Notably, Universitas Indonesia contributes to the accumulation of residual waste at TPA Cipayugn Depok, which has become increasingly concerning over time. The analysis in this study employs the Analytical Hierarchy Process (AHP) and Fuzzy Technique for Order Performance by Similarity to Ideal Solution (TOPSIS) methods to evaluate suitable waste management technologies for addressing the issues of residual waste accumulation. Additionally, techno-economic analysis is conducted to assess the feasibility of the selected technology. The project's feasibility evaluation parameters include Net Present Value (NPV), Internal Rate of Return (IRR), Payback Period (PBP), and Benefit Cost Ratio (BCR).